Gemcitabine Compared With Gemcitabine and S-1 Combination Therapy in Advanced Pancreatic Cancer. Issue 35 (September 2015) - Li, Doudou; Chen, Changhao; Zhou, Yu; Chen, Rufu; Fan, Xinxiang; Bi, Zhuofei; Li, Zhihua; Liu, Yimin; Holger, Cramer.
<x xml:space="preserve">Abstract</x> Abstract Several reports suggest that gemcitabine (GEM) plus S-1 combination (GS) is associated to prolong the survival in patients with unresectable pancreatic cancer (PC). We conducted a systemic review and meta-analysis of studies comparing the safety and efficacy of GS versus GEM. Summary data from randomized trials and retrospective studies were searched in PubMed, EMBASE, Web of Science, and the Cochrane Library. Statistical analyses were conducted to calculate the hazard ratios (HRs) and relative risk (RR) with 95% confidence intervals (CIs) using random-effects models. Subgroup analyses based on the chemotherapy cycles were performed to explore the efficacy and toxicity for therapy. Sensitivity analyses were conducted by removing specific studies to assess the effects of study quality. Between January 2004 and August 2012, 4 RCTs and 2 retrospective studies including a total of 1025 cases were identified. The overall survival (OS) (HR: 0.82; 95% CI, 0.70–0.96; P = 0.01) and progression-free survival (PFS) (HR: 0.65; 95% CI, 0.55–0.77; P < 0.001) for the GS arm were significantly longer than the GEM arm. The differences in objective response rate (ORR) (RR: 1.24; 95% CI, 1.17–1.33; P < 0.001) and disease control rate (DCR) were also better in the GS arm (RR: 1.37; 95% CI, 1.19–1.59; P < 0.001). Grades 3 to 4 toxicities in both the groups were similar except neutropenia and diarrhea, which were more frequent in the GS arm (P < 0.001). In the subgroup analysis, the cycle for chemotherapy every 4 weeks has equivalent efficacy and less toxicity than regimens every 3 weeks in the GS arm. The current meta-analysis suggested that GEM significantly prolonged OS and PFS when added to S-1 combination in patients with unresectable PC. GS therapy also offers better ORR and DCR than GEM monotherapy and no unexpected toxicity was evident.